Assessing the impact of peer-to-peer energy trading on financial benefits and autonomy in local communities using an agent-based model - Simon, Fabian Tim (2025)
This thesis explores the transformative potential of Peer-to-Peer (P2P) energy trading as an extension to existing centralized systems, where energy is distributed exclusively by the utility company. Using agent-based modeling (ABM), the study simulates interactions between prosumers, consumers, and utility providers to examine the benefits of P2P trading. The findings reveal that P2P trading provides financial benefits, enhances energy autonomy by enabling local energy use, and improves energy resilience by decreasing reliance on centralized grids. These insights provide actionable recommendations for end-users, policymakers, and utilities, highlighting the role of P2P systems in advancing a decentralized and consumer-driven energy transition.